2018
DOI: 10.1111/asj.13033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tributyrin supplementation on ruminal microbial protein yield, fermentation characteristics and nutrients degradability in adult Small Tail ewes

Abstract: Two trials were conducted to assess the effects of tributyrin (TB) supplementation on ruminal microbial protein yield and fermentation characteristics in adult sheep. In an in vitro trial, substrate was made to offer TB at 0, 2, 4, 6, and 8 g/kg on a dry matter (DM) basis and incubated for 48 hr. In an in vivo trial, 45 adult ewes were randomly assigned by initial body weight (55 ± 5 kg) to five treatments of nine animals over an 18-day period. Total mixed ration was made to offer TB to ewes at 0, 2, 4, 6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For SB, our results are supported by research that indicates a decrease in fiber digestibility in the rumen of sheep (Górka et al, 2017;Górka et al, 2018b,c). However, Ren et al (2018) observed an increase in NDF digestibility in sheep supplemented with tributyrin, whereas Rice et al (2019) observed no difference in fiber digestibility in heifers supplemented with unprotected SB.…”
Section: Discussionmentioning
confidence: 87%
“…For SB, our results are supported by research that indicates a decrease in fiber digestibility in the rumen of sheep (Górka et al, 2017;Górka et al, 2018b,c). However, Ren et al (2018) observed an increase in NDF digestibility in sheep supplemented with tributyrin, whereas Rice et al (2019) observed no difference in fiber digestibility in heifers supplemented with unprotected SB.…”
Section: Discussionmentioning
confidence: 87%
“…These results indicated that TB supplementation in feed was effective in enhancing fish performance, at least in Megalobrama amblycephala. Researchers have demonstrated the availability and functionality of TB supplemented in the feed of terrestrial animals, such as broiler chickens (9, 10), weaned pigs (11), and small tail sheep ewes (12). Among aquatic animals, the effects of TB supplementation in feed have also been assessed in some fish species.…”
Section: Effect Of Tb Supplementation On Growth and Whole-body Compositionmentioning
confidence: 99%
“…Hence, TB has a function similar to that of butyric acid. Some studies have shown that TB has a positive effect on growth performance in various terrestrial animals, such as broiler chickens (1,9), weaned pigs (10,11), and small tail sheep ewes (12). In addition, TB can promote the healthy development, digestion and collection of nutrients of the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more butyrate molecules can be released in the intestine where they exert their functions. Several studies have been conducted in which TB supplementation was used in various terrestrial animals, such as piglets (Dong et al, ; Hou, Liu, Hu, & Shen, ), small tail ewes (Ren et al, ) and broilers (Antongiovanni et al, ; Li et al, ; Lum et al, ). The results of these studies were consistent and demonstrated that TB promotes growth performance and maintains normal intestinal morphology of animals.…”
Section: Introductionmentioning
confidence: 99%